ASAL-USUL DAN EKSPANSI ALAM SEMESTA: STUDI KOMPARATIF ANTARA KOSMOLOGI MODERN DAN TAFSIR ILMI KARYA MIR ANEESUDIN - Aan Anisa; Esti Rahmawati; Rajib Daffa Al-Fikri; Andi Rosa (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
The study of the relationship between the Qur'an and modern science continues to develop alongside advances in scientific knowledge, particularly in astronomy and cosmology. One scholar who sought to integrate these two domains is Dr. Mir Aneesuddin through his work A Pocket Guide to Quran and Science. This study aims to analyze Mir Aneesuddin's views on the origin and expansion of the universe and compare them with modern cosmological theories. The research employs a qualitative approach using library research. Primary data are derived from Mir Aneesuddin's work, while secondary data consist of cosmological literature, scientific journals, and studies on scientific exegesis (tafsir ilmi). The analysis is conducted through a thematic-comparative (maudhū‘ī-muqāran) approach using descriptive-analytical and interpretative methods. The findings reveal that Mir Aneesuddin interprets the concepts of ratq and fataq in Qur'an 21:30 as indications of an initially unified universe that later underwent separation and development, conceptually corresponding to the Big Bang theory. Furthermore, the concept of lamūsi‘ūn in Qur'an 51:47 is understood as an indication of the universe's continuous expansion, which aligns with the expanding universe theory. However, the study also finds significant differences between modern cosmology and Aneesuddin's scientific exegesis in terms of epistemology, methodology, and objectives. Modern cosmology is based on empirical observation and scientific verification, whereas scientific exegesis is grounded in revelation as the primary source of knowledge. This study concludes that Mir Aneesuddin's thought provides a constructive framework for dialogue between revelation and science, allowing both to complement one another in explaining the reality of the universe.